Fungal Reproduction and Growth - Sultan, Sadia; Kaur Surindar Singh, Gurmeet (IntechOpen, 2022)
One of the largest and most diverse kingdoms in eukaryotes is fungi, which consists of approximately 2.2-3.8 million species. This book provides readers with an in-depth understanding of fungi diversity and the role of fungi in the ecosystem. Chapters address such topics as fungi reproduction and pathology, fungal mycotoxicity, fungi mating mechanisms, and much more.